Caring for Children With Medical Complexity in the Early COVID-19 Pandemic in an Ambulatory Primary Care Setting - Driansky, Allison; Pilapil, Mariecel; Bianco, Kristina; Steinway, Caren; Feigenbaum, Sheri; Yang, Anna; Jan, Sophia (Frontiers in Pediatrics, 2022)
Background Children with medical complexity (CMC) have multiple chronic conditions and require a high level of coordinated healthcare. The risk of COVID-19 among CMC is unclear. Objectives We aim to identify and describe the prevalence and experience of COVID-19 among CMC and their caregivers during the initial weeks of the COVID-19 pandemic in the NY metropolitan area. Methods We performed a cross-sectional study of children enrolled in a structured clinical program for CMC at a large urban, academic general pediatrics practice in NY. Results In our patient population (n = 132), 16 patients had a known exposure with parents being the most common exposure in 37.5% (n = 6). Two patients were hospitalized for COVID-19 while the remainder of the confirmed or suspected COVID-19 cases were managed as an outpatient. Conclusions Common sources of COVID-19 exposure were family members and home care providers. Almost all of our patients experienced interruption of medical care including missed therapies and visits.